Production and use of a hemagglutinin for detecting antibody to Jamestown Canyon virus. - Grimstad, P R (1987)
A procedure was developed for producing a hemagglutinin for the California serogroup (family Bunyaviridae, genus Bunyavirus) virus Jamestown Canyon, a human pathogen. Serum samples from humans putatively infected with this virus or with La Crosse virus were tested by hemagglutination inhibition. Each antigen detected antibody to the respective virus, with little cross-reactivity. These results suggest that both antigens should be used when the hemagglutination inhibition test is applied to the diagnosis of human infections with California serogroup viruses in North America.